Meeting report: BioMolViz workshops for developing assessments of biomolecular visual literacy. Issue 2 (11th September 2020) - Procko, Kristen; Engelman, Shelly; Jakubowski, Henry; Beckham, Josh T.; Dean, Diane M.; Franzen, Margaret A.; Novak, Walter R. P.; Roberts, Rebecca; Roca, Alberto I.; Shor, Audrey C.; Terrell, Cassidy R.; Dries, Daniel R.
Abstract: While molecular visualization has been recognized as a threshold concept in biology education, the explicit assessment of students' visual literacy skills is rare. To facilitate the evaluation of this fundamental ability, a series of NSF‐IUSE‐sponsored workshops brought together a community of faculty engaged in creating instruments to assess students' biomolecular visualization skills. These efforts expanded our earlier work in which we created a rubric describing overarching themes, learning goals, and learning objectives that address student progress toward biomolecular visual literacy. Here, the BioMolViz Steering Committee (BioMolViz.org ) documents the results of those workshops and uses social network analysis to examine the growth of a community of practice. We also share many of the lessons we learned as our workshops evolved, as they may be instructive to other members of the scientific community as they organize workshops of their own.